Gender-Responsive Islamic Sexuality Education: A Comparative Study of Ulwan and At-Tihami - Abdul Fatah (WISE Pendidikan Indonesia, 2026)
This study examines Islamic sexuality education through a comparative analysis of Abdullah Nasih Ulwan’s Tarbiyat al-Awlad fi al-Islam and Muhammad At-Tihami’s Qurrat al-‘Uyun. Using qualitative document-based research, the study analyzes each scholar’s views on the aims, content, developmental orientation, and social function of sexuality education. The findings show that both perspectives frame sexuality education as a value-based process integrating religious literacy, moral formation, bodily awareness, self-protection, and responsible family relationships. Ulwan emphasizes a developmental and preventive approach, including privacy etiquette, modesty, age-appropriate guidance, puberty education, separation of sleeping arrangements, and protection from harmful sexual stimuli. In contrast, At-Tihami situates sexuality education primarily within marital ethics, relational responsibility, emotional intimacy, and family well-being. The study’s novelty lies in integrating these complementary perspectives into a gender-responsive Islamic safeguarding framework that connects child and adolescent protection with healthy marital and family life. The findings suggest that Islamic Religious Education can provide culturally grounded guidance for preventing sexual violence, strengthening bodily autonomy, and promoting responsible sexuality education in families, schools, and community-based religious institutions.